Portable Gentle Jogger Improves Glycemic Indices in Type 2 Diabetic and Healthy Subjects Living at Home: A Pilot Study - Jose A. Adams; Veronica Banderas; Jose R. Lopez; Marvin A. Sackner (Journal of Diabetes Research)
Background. Physical inactivity is a high-risk factor for type 2 diabetes. Increased physical activity improves indices of glycemic control. Continuous glucose monitoring (CGM) allows the investigation of glycemic control during activities of daily living. A pilot study was undertaken to determine the effects of the portable Gentle Jogger (passive simulated jogging device (JD)) that decreases physical inactivity by effortlessly producing body movements on glycemic indices of healthy and type 2 diabetes subjects using CGM during activities of daily living. Methods. A single-arm, nonblinded study was carried out in 22 volunteers (11 type 2 diabetics and 11 healthy subjects), using continuous glucose monitoring (CGM) for 14 days. On day 4, subjects were provided with JD and instructed to use it a minimum of 3 times per day for 30 min for 7 days. CGM data was analyzed at baseline (BL) and during 2, 3, 4, 5, 6, and 7 days of JD (JD 2, 3, 4, 5, 6, 7) and 1-2-day post JD (Post JD1 and 2) and the following 24 hr indices computed mean glucose (mGLu), SUM of all glucose values, % coefficient of variation (%CV), area under the 24-hour curve (AUC), time spent above range (TAR, glucose 180-250 mg/dl), and time in range (TIR). Results. In healthy subjects, there were significantly lower values of mGlu and SUM compared to BL for all days of JD usage. In type 2 diabetics, mGlu, SUM, and AUC were significantly lower compared to BL, for all days of JD usage and Post JD1. TAR was significantly lower and TIR significantly improved during JD, in type 2 diabetics without change in %CV. Conclusion. Gentle Jogger is a portable, passive movement technology that reduces physical inactivity while improving 24 hr glycemic control. It can be self-administered as a standalone device or as an adjunct to diabetic medications. This trial is registered with NCT03550105.